PTU-072 The influence of iron supplementation on the severity of a murine model of colitis. (22nd June 2015) - Mahalhal, A; Reade, S; Campbell, B; Pritchard, DM; Probert, C
Abstract : Introduction: Iron deficiency anaemia is a common complication in inflammatory bowel disease (IBD). There is evidence that iron supplementation induces inflammation both in normal rats and in rodent models of IBD (Carrier J et al, Aliment Pharmacol Ther. 2001 Dec; 15(12): 1989–99.). Changes in the gut microbiota [dysbiosis] are common in IBD patients, but the mechanism is unclear. Iron may be a factor, as it is a growth factor for some bacteria. We have therefore investigated the effect of dietary iron intake upon a murine model of colitis. Method: Animal studies were performed on 6 groups of female C57BL/6 mice. Acute colitis was induced with 2% Dextran Sodium Sulphate (DSS) for 5 days in drinking water before go back on a normal water for a another 5 days. Two modifications of diet (normal chow 200 ppm iron) were used: low iron (100 ppm) and high iron (400 ppm). The groups were 1 controls; 2 acute DSS normal diet; 3 acute DSS with low iron diet for 10 days; 4 acute DSS with high iron diet for 10 days; 5 low iron diet for 4 weeks; 6 high iron diet for 4 weeks. Daily weight and clinical features were logged. Histology was performed at day 10 for groups 1–4 and day 28 for the rest. Colitis was scored using the Bauer score (Bauer et al, Gut 2010; 59:9 1192–1199). Faecal Calprotectin measured by ELISA (Biohit Healthcare Ltd.), and faecal iron by immunoassay. One ANOVA and t tests were performed to compare groups or pairs of samples. Results: Weight loss: DSS induced colitis in groups 2–4; it was most severe in the low iron group. Mean changes in weight were +4% in control, -5.3% in group 2, -9.2% in group 3, and -1% in group 4. Post-hoc testing showed p values of 0.0005, 0.16 and 0.01 for low iron diet vs groups 1, 2 and 4, respectively. Histology: mean colitis scores were; 0, 1.4, 1.9, 1.4, 0, 0 for groups 1–6, respectively. The score to low iron DSS mice was significantly worse than that in untreated mice and marginally worse than those on normal or high iron diets. Calprotectin: calprotectin concentrations were greatest in DSS mice on the low iron diet. Faecal iron: this was increased in a dose-dependent manner within 4 weeks in the groups of mice that did not receive DSS. In DSS treated mice, the low iron diet mice resulted in the highest faecal iron results p = 0.010, 0.0024, and 0.0019 for groups 1, 2 and 4 respectively. Conclusion: Clinical observation and histological scoring showed that a low iron diet exacerbated DSS colitis. Mice consuming 50% of the normal amount of iron lost more weight and developed more severe colitis than other mice given DSS. The high iron diet had no measureable effect on the severity of DSS colitis. We will now investigate the effects of iron on the intestinal microbiota in the 6 groups. Disclosure of interest: None Declared.